Barn og unges hverdagssteder i endring - Vogt, Kristoffer (Nordic Journal of Comparative and International Education (NJCIE), 2019)
This article describes the ways in which children and young people’s everyday places have changed in the course of the Post-war period in Norway and suggests some opportunities and constraints arising from these changes. The analysis is based on biographical interviews with three generations in 23 Norwegian families, in addition to a wide selection of relevant research and statistics. Children and young people’s everyday places have become more institutionalized, organized and digitalized, and neighbourhoods have become less important as sites of everyday interaction. This development has varying implications for different groups of young people. Those who experience failure in school are in the greatest need of experiences of mastery in other areas. Recruitment to organized leisure activities is closely related to parental resources, and whereas experiences of household work previously could point the way into prac-tical occupations, many practically inclined young people now lack direction, opportunities and motiva-tion, except for different varieties of consumption. The mastery experienced in today’s everyday places can be relevant and valuable in the labour market, albeit in different ways than the building, tinkering and care work of previous periods.